Variation of urinary protein to creatinine ratio during the day in women with suspected pre‐eclampsia. (25th April 2014) - Verdonk, K; Niemeijer, IC; Hop, WCJ; de Rijke, YB; Steegers, EAP; van den Meiracker, AH; Visser, W
<x xml:space="preserve">Abstract</x> Objective To investigate the stability throughout the day of the protein to creatinine ratio (PCR) in spot urine, to demonstrate whether the PCR is a valid alternative for 24‐hour protein investigation in pregnant women. Design Prospective study. Setting Tertiary referral university centre. Population Women suspected of having pre‐eclampsia, admitted to the Erasmus Medical Centre. Methods Twenty‐four‐hour urine collections and simultaneously three single voided 5‐ml aliquots were obtained at 8 a.m., 12 a.m. (noon) and 5 p.m. A PCR was measured in each specimen and compared with the 24‐hour protein excretion. Main outcome measures The 24‐hour proteinuria and PCR measured in spontaneous voids. Results The PCRs correlated strongly with each other and with the 24‐hour protein excretion but did show variation throughout the day (mean coefficient of variation 36%; 95% confidence interval 31–40%). The coefficient of variation was unrelated to the degree of 24‐hour proteinuria. Receiver operating characteristics curves to discriminate between values below and greater than or equal to the threshold of 0.3 g protein per 24‐hour had an area under the curve of respectively 0.94 (8 a.m.), 0.96 (noon) and 0.97 (5 p.m.). Sensitivities at 8 a.m., noon and 5 p.m. were respectively 89%, 96% and 94%; specificities were 75%, 78% and 78% with the proposed PCR cut‐off of 30 mg/mmol (0.26 g/g) (National Institute for Health and Care Excellence guidelines).There is no evidence of a difference between the three measurement times regarding the sensitivities and specificities. Conclusion The PCR determined in spot urine varies throughout the day but is a valid alternative for 24‐hour urine collections in pregnant women. It is especially useful to rapidly identify clinically relevant proteinuria.